Pengaruh Harga Minyak Mentah, Tingkat Suku Bunga Bank Indonesia, 1 dan Kurs Rupiah/USD Terhadap Harga Saham PT Aneka Tambang Tbk. Periode 2010 - 2014 - Janny Rowena (Universitas Multimedia Nusantara, 2016)
This study was conducted to examine the influence of the Indonesian Crude Price, BI rate, and exchange rate of Rupiah/USD to PT Aneka Tambang, Tbk. stock price for period 2010 – 2014. There are four variables : stock price as the dependent variable, while the Indonesian crude price, BI rate, and exchange rate of Rupiah/USD as the independent variables. The analysis technique used in this research is multiple linier regression. Based on statistical ttest, Indonesian crude price and exchange rate of Rupiah/USD have significant influenced on stock price because the significant value is less than 0.05. Meanwhile, BI rate doesn’t have a significant influence because the significant value is more than 0.05. Based on statistical F test indicates that the Indonesian Crude Price, BI rate, and exchange rate of Rupiah/USD are simultantly affect to PT Aneka Tambang, Tbk. stock price. Result of coefficient determination test showed that Indonesian Crude Price, BI rate, and exchange rate of Rupiah/USD explained PT Aneka Tambang, Tbk stock price 70.9% and the rest (29.1%) is influenced by other variables outside the model. Keywords: Indonesian Crude Price (ICP), BI rate, exchange rate, stock price